Analisis Pengelolaan dan Pencatatan Akuntansi pada Lembaga Amil Zakat Solopeduli - Baiti, Qonita Nur (IAIN Surakarta, 2018)
This research aims to analyze the management and recording system of accounting for the Amil zakat Solopeduli institution. With a qualitative descriptive approach, the data in this study was obtained by interview methods and documentation. The literature study of PSAK 109 is also conducted as reference for accounting records of Amil Zakat institution. The results of this research show that Infak funds, Zakat, and charity have been well managed and have been in accordance with sharia principles. The institution of Amil Zakat Solopeduli has also been doing good accounting records and published through the website, Hadila magazine, and Solopos newspaper.Keywords: accounting, governance, LAZ